(1081) Economy of Education series -Bratislava School of Economics Czechosiovakiaسلسلة اقتصاد التعليم - Andrej Kamiac (معهد التخطيط القومي, 2026)
This study explores the evolving paradigm of education from a purely humane-cultural domain managed exclusively by pedagogists to a critical economic dimension essential for modern societal growth. The author argues that as classical development sources face exhaustion, science and education emerge as inexhaustible forces that transform natural resources into productive capabilities, positioning education as a core driver of the scientific-technical revolution. To analyze this integration, the text bifurcates the "economy of education" into two primary dimensions: external and internal. The external economy focuses on macro-level relationships between education and economic development, examining public investment allocations, financing structures, and the long-term forecasting of qualified manpower to meet societal needs. Conversely, the internal economy applies the law of time economy and work efficiency directly to the school system, addressing macro-management, optimal school distribution, institutional organization, resource utilization, and the rationalization of teaching curricula. Kamiac emphasizes that the rapidly escalating global demand for education—driven by population growth, adult lifelong learning, and heightened qualitative standards—requires immense financial and technical support, which is naturally constrained by national economic limits. Consequently, the study advocates for bridging the traditional gap and aversion between economists and educationalists. Rather than exerting administrative curation, economists must foster a collaborative atmosphere that encourages educational innovation, pushing past conservative methodologies toward modern, effective techniques that optimize national resource utilization while enhancing educational quality . اتناول هذه الدراسة التحول النوعي في مفهوم التعليم من مجرد مجال إنساني وثقافي خالص يقع تحت المظلة الحصرية لعلماء التربية، إلى أداة اقتصادية حيوية تسهم في التنمية المجتمعية الشاملة. ويوضح الكاتب أنه مع محدودية الموارد التنموية الكلاسيكية، تبرز العلوم والتعليم كقوى غير محدودة وقابلة للتجدد لتحويل القوى الطبيعية إلى قوى إنتاجية، مما يجعلهما من ركائز الثورة العلمية والتقنية الحديثة. ومن هذا المنطلق، تُقسّم الدراسة علم اقتصاديات التعليم إلى شقين رئيسيين: الاقتصاد الخارجي والاقتصاد الداخلي؛ حيث يركز "الاقتصاد الخارجي للتعليم" على دراسة العلاقات الكلية بين منظومة التعليم والتنمية الاقتصادية، مقيّمًا حجم الاستثمارات المجتمعية الموجهة للتعليم، ومصادر التمويل، وقياس العائد الاقتصادي الفعلي، بالإضافة إلى استشراف الاحتياجات المستقبلية من العمالة المؤهلة. وفي المقابل، يعتني "الاقتصاد الداخلي للتعليم" بتطبيق قانون اقتصاد الوقت وكفاءة العمل داخل المنظومة التعليمية نفسها، من خلال تنظيم الإدارة الماكروية للمدارس، وتحديد أحجامها المثالية، وتوزيعها الجغرافي، فضلاً عن تطوير المناهج الدراسية وهياكلها التعليمية لترشيد النفقات وتحسين جودة العملية التعليمية. ويؤكد الباحث أن التزايد المتسارع في الطلب العالمي على التعليم — نتيجة النمو السكاني والإقبال على التعلم المستمر — يفرض ضغوطًا مالية وتقنية كبيرة على ميزانيات الدول؛ مما يستوجب البحث عن آليات مبتكرة لرفع الكفاءة التعليمية بالاعتماد على التطور العلمي. وفي الختام، يشدد كامياك على ضرورة إزالة الفجوة والنفور التقليدي بين التربويين والاقتصاديين، مؤكدًا أن دور الاقتصادي لا يهدف إلى فرض وصاية إدارية بل إلى خلق مناخ تعاوني يحفز الابتكار التعليمي والتخلي عن الأساليب التقليدية المحافظة لصالح تقنيات حديثة تضمن الاستغلال الأمثل للموارد الوطنية.